Feeling Identified vs. Behaving as Such: A Multi-Study Project on Chinese Organizational Identification and Chinese Employees’ Identification Profiles - Yang, Jie; Nguyen, Hannah-Hanh D.; Xiong, Xiaobin; Wang, Xinyan (Frontiers in Psychology, 2019)
We conducted a multi-study, field research program to (a) develop, validate and cross-validate an emic-etic, bi-dimensional measure of Chinese workers’ organizational identification (OID) based on our previously conceptualized framework, and (b) classify employees into three levels of OID. We found convergent evidence showing the Chinese OID construct consists of emotional and behavioral dimensions. Specifically, in Study 1 (N = 408), we developed and validated a bi-dimensional measure called the Chinese Organizational Identification Questionnaire (COIQ; 8 items). In Study 2 (N = 299), we cross-validated the COIQ and established the construct validity by examining several hypothesized relationships between the Chinese OID construct and other relevant organizational variables, such as unethical pro-organizational behavior, perceived psychological contract violation, and perceptions of business practices of compensations and benefits. Based on the factor analytic and structural equation modeling results, we concluded that the bi-dimensional Chinese OID model as measured with the COIQ has construct validity. More importantly, we used the latent profile analysis method to generate three OID profiles of Chinese workers based on their COIQ scores: The Strong Identifier, the Moderate Identifier and the Action-Oriented Identifier. Those profiles were differentially related to the organizational constructs of interest. The implications for researchers and practitioners were discussed.